(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
أثر بعض مؤشرات الواقع الاقتصادي للمرأة الريفية على التنمية المستدامة في منطقة القرداحة ابراهيم حمدان صقر محمد العبد الله صوفيا مالك نعامة عمل المرأة الريفية، مشاركة المرأة في البرامج التنموية) على التنمية المستدامة في منطقة القرداحة. ولتحقيق أهداف البحث، والإجابة على تساؤلاته، اعتُمد في جمع البيانات المُتعلقة بالمُوضوع على الأدبيَّات والدراسات السَّابقة ذات الصلة، أمَّا الإطار العملي فقد اعتُمد على إعداد استبيان تمَّ تصميمه لهذا الغرض، وقامت الباحثة بإجراء التحليلات اللازمة واختبار فرضيَّات البحث، وتوصَّل إلى مجموعة من الاستنتاجات والتوصيات، أهمها: • وجود أثر ذو دلالة إحصائية لمؤشرات الواقع الاقتصادي (حيازة المرأة للأرض الزراعية، عمل المرأة الريفية، مشاركة المرأة في البرامج التنموية) على عملية التنمية المستدامة في منطقة البحث، وقد بلغت قوة العلاقة 0.773، ومعامل التحديد 0.598. • وجود تأثير معنوي لكل من العوامل المُتغيرة (حيازة المرأة للأرض الزراعيَّة، عمل المرأة الريفيَّة، مُشاركة المرأة في البرامج التنموية) على المتغير المستقل (التنمية المستدامة) كل على حدة، إلا أنَّ قوة العلاقة بينهم قد اختلفت تبعاً للعامل المدروس، فقد بلغت قوة العلاقة بين كل من العوامل المتغيرة المذكورة سابقاً، والعامل المستقل (0.801، 0.793، 0.613) على الترتيب. وقد أوصى البحث بضرورة التأكيد على حق المرأة في إرث العائلة، توسيع رقعة البرامج التنموية، الهادفة إلى تعليم المرأة الريفية لتُغطي بقعة جغرافيَّة أكبر من المجتمع الريفي، والسعي لتعزيز ثقافة عمل المرأة خارج المنزل، تشجيع متابعة البحث في مجال تأثير مؤشرات الواقع الاقتصادي على عملية التنمية المستدامة. This study aime to demonstrate and analyze the impact of some indicators of the economic reality of rural women (women’s acquisition of agricultural land, rural women’s work, women’s participation in development programs) on sustainable development in the Qardaha region. In order to achieve the objectives of the research, and to answer its questions, it was adopted in the collection of data on the subject on the literature and previous studies related to the practical framework was based on the preparation of a questionnaire designed for this purpose, the researcher conducted the necessary analysis and test hypotheses research, and reached a set of conclusions and recommendations, The most important: • There was a statistically significant impact on the sustainable development process in the research area (women’s possession of agricultural land, rural women’s work, women’s participation in development programs). The strength of the relationship was 0.773, and the coefficient of selection was 0.598. • There was a significant effect on the independent variable (sustainable development) for each of the variable factors (women’s possession of agricultural land, rural women’s employment, women’s participation in development programs), but the strength of their relationship differed according to the studied factor. The relationship between each of the previously mentioned variables, the independent factor (0.801, 0.793, 0.613), respectively. It was recommended to emphasize the right of women to inherit the family, to expand the scope of development programs aimed at educating rural women to cover a larger geographical area of ​​rural society, to promote the culture of women working outside the home, and The impact of indicators of economic reality on the process of sustainable development.